Spain : Financial Sector Assessment Program-Technical Note-Stress Testing Banking System Resilience. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the results of the stress testing of banking system resilience in Spain. The results indicate that some banks may have difficulty enduring additional pressures on their profitability. In addition, some banks are vulnerable to market losses arising from a rapid increase in interest rates, given their significant exposures to fixed income securities. Near-term funding and liquidity risks seem limited, but funding challenges are likely to grow. Several banks are heavily reliant on central bank funding. Based on these findings, the authorities are encouraged to continue to monitor closely interest rate and government bond market risks in their stress testing exercises.